Functional ecology of soil microbial communities along a glacier forefield in Tierra del Fuego (Chile) - Fernandez-Martinez, Miguel A.; Pointing, Stephen B.; Perez-Ortega, Sergio; Arroniz-Crespo, Maria; Allan Green, T. G.; Rozzi Marin, Ricardo Roberto; Sancho, Leopoldo G.; de los Rios, Asuncion (My University, 2016)
A previously established chronosequence from Pia Glacier forefield in Tierra del Fuego (Chile) containing soils of different ages (from bare soils to forest ones) is analyzed. We used this chronosequence as framework to postulate that microbial successional development would be accompanied by changes in functionality. To test this, the GeoChip functional microarray was used to identify diversity of genes involved in microbial carbon and nitrogen metabolism, as well as other genes related to microbial stress response and biotic interactions. Changes in putative functionality generally reflected succession-related taxonomic composition of soil microbiota. Major shifts in carbon fixation and catabolism were observed, as well as major changes in nitrogen metabolism. At initial microbial dominated succession stages, microorganisms could be mainly involved in pathways that help to increase nutrient availability, while more complex microbial transformations such as denitrification and methanogenesis, and later degradation of complex organic substrates, could be more prevalent at vegetated successional states. Shifts in virus populations broadly reflected changes in microbial diversity. Conversely, stress response pathways appeared relatively well conserved for communities along the entire chronosequence. We conclude that nutrient utilization is likely the major driver of microbial succession in these soils.
Keywords: functional genes; antibiotic resistance; geochip microarray; primary succession; chronosequence